Primitive Distal Duodenal Caucer. Duodenectomy - Beguiristain, Alberto; Bogliaccini, Gustavo; Praderi, Raúl (Cirugía del Uruguay, 1980)
Report of one case of anular adenocarcinoma in the fourth portian of duodenum, in which diagnosis was established radiologically. This condition shoul'd be suspected when megaduodenum in the first and second portion is apparent.